clinical effects of chlorhexidine mouth washes on patients undergoing orthodontic treatment - AL-Ruayee, mehdi Abdul-Hadi; Hassan, Zayed S. (Journal of the Faculty of Medicine Baghdad, 2008)
Backround: chlorhexidine mouth wash one of the effective chemical plaque control method that is used to prevent plaque accumalation and subsequent gingivitis.